PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF SISTEM PENCERNAAN MANUSIA MENGGUNAKAN UNITY 3D DI SD NEGERI 5 CIHONJE - Pratama, Bayu Rizkya (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2024)
Learning media always follow technological developments. One example is the use of 3D animation, which makes the process of delivering information easier and more engaging to understand. The purpose of this study is to design and develop interactive learning media on the human digestive system to improve student achievement at SD Negeri 5 Cihonje, as well as to assess the performance and feasibility of this learning media. Currently, the learning media used in teaching science about the human digestive system at SD Negeri 5 Cihonje still relies on books and direct explanations from teachers through lectures, which is considered less optimal in delivering the material. Therefore, there is a need for alternative media, such as interactive multimedia-based learning media. This rationale led the author to develop new learning media on the human digestive system. The development method used is the multimedia development life cycle (MDLC) method, as proposed by Luther-Sutopo, which involves six stages: concept, design, material collection, production, testing, and distribution. The outcome of this study is an interactive multimedia tool designed to assist in the learning process of the human digestive system at SD Negeri 5 Cihonje.